Metal oxide charge transport layers in perovskite solar cells—optimising low temperature processing and improving the interfaces towards low temperature processed, efficient and stable devices. (15th December 2020) - Wang, Yantao; Djurišić, Aleksandra B; Chen, Wei; Liu, Fangzhou; Cheng, Rui; Ping Feng, Shien; Ng, Alan Man Ching; He, Zhubing
Abstract: In this review, we will discuss recent progress in metal oxide charge transport layers in perovskite solar cells (PSCs). While a large number of PSCs have at least one metal oxide charge transport layer, here we focus on the progress towards the achievement of high efficiency devices with metal oxide layers prepared under mild deposition conditions, with the ultimate goal being the devices containing metal oxide layer both below and above the perovskite layer to achieve improved stability. Thus, we will provide an overview of recent progress in metal oxides deposited below the perovskite layer (electron transport layers in conventional architecture PSCs, hole transport layers in inverted architecture PSCs), followed by the progress in devices containing both top and bottom metal oxide charge transport layer, and briefly introducing other possible uses of metal oxides in PSCs. For these various applications of metal oxides, we will discuss different approaches (doping, surface treatments, interface modifications) commonly employed to improve device performances, and finally we will provide a brief overview of the characterisation techniques commonly employed to obtain insights into physical mechanisms responsible for the observed device performance. While for several of the experimental techniques extensive reviews exist, this is not the case for all the techniques, and the perovskite literature commonly lacks cautions in interpretation, guidelines on avoiding artefacts, and general overview of what techniques need to be employed for comprehensive device characterisation.